Pemberdayaan Masyarakat Menuju Desa Siaga Melalui Usaha Promotif dan Preventif - Kusuma, Adi Mulya; Ibrahim, Yok; Bhakti, Fadel Maulana; Ramadhany, Gilang Alfisyar; Fiyani, Putri Ohkta; Rahmawati, Ainur; Nuryana, Nuryana; Fadhilah, Muslimatul; Ardiansyah, Dicky; Achmad, Novie Daniah Ridwan; Saputra, Akhmad Andi (Universitas Methodist Indonesia, 2024)
Community empowerment is an effective strategy to address socio-economic and health issues. In Indonesia, this concept is implemented through the development of resilient and self-sufficient villages. The Community Service Program (KKN) plays a vital role in supporting this empowerment through promotive and preventive efforts. This article discusses the KKN activities in Kambingan Village, Cerme District, Gresik Regency, which include health education, cleanliness campaigns, nutrition education, Basic Life Support (BLS) training, and other preventive activities. The results achieved include increased community awareness and knowledge about the importance of health, improved first aid skills, and economic empowerment through MSME training.